HYDROCEPHALUS: OVERVIEW AND PERSPECTIVES - A.V. Ciurea; F.M. Brehar; A. Tascu (Amaltea Medical Publishing House, 2010)
Cerebrospinal fl uid (CSF) is produced by choroid plexus, circulates in the subarachnoid space and the resorbtion occurs at the level of arachnoid granulation. Ventricular enlargement appears because of: 1exces of CSF production, 2. altered CSF fl ow or resorbtion, 3. secondary post-traumatic, and 4. post-aneurysmal SAH, with or without symptoms or neurologic impairment. Hydrocephalus (HY) (count in infants 3-5 / 1.000 new-born) represents the excess of CSF in ventricles or subarachnoidal space and is commonly associated with meningomyelocele (MMC) & acqueductal stenosis. The most often clinical syndrome which occurs in hydrocephalus is Intracranian Hypertension syndrome, which consists in headache, vomitting and papilary edema. The diagnostic protocol is represented by neurological examination, ophtalmological examination, CT scan and MRI. Purposes of surgical procedures are to decrease ICP, to re-expand the brain and to prevent neuronal destruction. The main surgical procedures are endoscopic third ventriculostomy (ETV), ventriculoperitoneal shunt and ventriculoatrial shunt.